Evaluation of major depressive disorder using 7 Tesla phase sensitive neuroimaging before and after mindfulness-based cognitive therapy - Jakary, Angela; Lupo, Janine M.; Mackin, Scott; Yin, Audrey; Murray, Donna; Yang, Tony; Mukherjee, Pratik; Larson, Peder; Xu, Duan; Eisendrath, Stuart; Luks, Tracy; Li, Yan (Journal of affective disorders, 2023)
We applied 7 Tesla phase sensitive imaging to evaluate the impact of brain iron levels on depression severity and cognitive function in individuals with major depressive disorder (MDD) treated with mindfulness-based cognitive therapy (MBCT). Seventeen unmedicated MDD participants underwent MRI, evaluation of depression severity, and cognitive testing before and after receiving MBCT, compared to fourteen healthy controls (HC). Local field shift (LFS) values, measures of brain iron levels, were derived from phase images in the putamen, caudate, globus pallidus (GP), anterior cingulate cortex (ACC) and thalamus. Compared to the HC group, the MDD group had significantly lower baseline LFS (indicative of higher iron) in the left GP and left putamen and had a higher number of subjects with impairment in a test of information processing speed. In the MDD group, lower LFS values in the left and right ACC, right putamen, right GP, and right thalamus were significantly associated with depression severity; and lower LFS in the right GP was correlated with worse performance on measures of attention. All MBCT participants experienced depression relief. MBCT treatment also significantly improved executive function and attention. MBCT participants with lower baseline LFS values in the right caudate experienced significantly greater improvement in depression severity with treatment; and those with lower LFS values in the right ACC, right caudate, and right GB at baseline performed better on measures of verbal learning and memory after MBCT. Our study highlights the potential contribution of subtle differences in brain iron to MDD symptoms and their successful treatment. •Major depressive disorder (MDD) and healthy controls were evaluated using 7 T MRI.•MDD had increased iron deposition in the putamen and globus pallidus.•Mindfulness-based cognitive therapy (MBCT) improved depression and cognition•Baseline brain iron content can predict MBCT treatment efficacy.